Analisis Media Monitoring Terhadap Brand Air Mineral Le Minerale pada Bulan Maret-April 2024 - Mazaya, Witiashila Sani; Hafiar, Hanny; Priyatna, Centurion Chandratama (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Mineral water plays an important role in maintaining human health and life. It helps to keep the human body hydrated and maintain the function of organs, regulates body temperature, and helps in the process of digestion and absorption of nutrients. Le Minerale is present as bottled drinking water that is considered healthy and safe for consumption because it is BPA free. Furthermore, it also has quality and guaranteed quality content because it comes directly from mountain springs. This provides the consumer with a fresh, unique flavour characteristic, namely a sweet taste in the mineral water. The digital era, especially social media, which continues to grow rapidly, presents an increasingly complex challenge for Le Minerale. This encourages the need for efforts to conduct media monitoring to track and monitor positive sentiment, mentions, and reach on social media. The research method uses a descriptive qualitative netnography approach, utilising media monitoring analytical tools Brand24. The data collected by the Brand24 platform are derived from social media sources, including TikTok and Twitter.